ANALISIS PEMANFAATAN INFRASTRUKUR TEKNOLOGI INFORMASI UNTUK MENDUKUNG PROGRAM E-GOVERNMENT PADA KANTOR KEMENTERIAN AGAMA DI WILAYAH PROVINSI DI YOGYAKARTA - M. Didik R. Wahyudi (Kaunia: Integration and Interconnection Islam and Science, 2016)
The rapid development of information technology and almost all institutions have implemented information technology in the processing of data and information. Office of the minister of religion as government agencies committed to improving service to the community as well as providing actual information from the government in real-time. Therefore the use of information technology is needed to help employees do the work. The use of information technology in an institution due to several factors, such as social aspect, affect (feelings of people), complexity, long-term consequences, the suitability of the task and the conditions that facilitate the use of information technology. Based on these aspects, the research conducted to see the effect of the use of information technology to social factors, the complexity of the system and the conditions that facilitate the use of information technology on the religious ministries in the area of Yogyakarta Special Region.